Harmonized Data for Measuring the Effects of Weather Variability - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
As part of an IFPRI-funded project, raw and partially processed secondary data have been harmonized and analyzed to examine the effects of weather variability on household welfare, the latter measured using per capita total household expenditure. This cross-country project covers rural Ghana, Uganda, and Tanzania. Household survey data, a time series of monthly precipitation and temperature, as well as other biophysical data have been harmonized and analyzed using Stata software. Several Stata do files have been created for data processing and analysis as noted in the attached “READ ME.txt” file. The sources of household survey data are the following: National Household Budget Surveys and National Panel Surveys (for Tanzania); National Household Surveys and National Panel Surveys (for Uganda); and Ghana Living Standards Surveys (for Ghana). Precipitation data are obtained from the Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS). Temperature data are obtained from the Center for Climatic Research at the University of Delaware. Other landscape-level biophysical data analyzed include night lights, population density, and agroecological zones (AEZ).